2002
DOI: 10.1074/jbc.m106186200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of STEF, a Guanine Nucleotide Exchange Factor for Rac1, Required for Neurite Growth

Abstract: Accumulating evidence suggests that Rho family GTPases play critical roles in the organization of the nervous system. We previously identified a guanine nucleotide exchange factor of Rac1, STEF (SIF and Tiam 1-like exchange factor), which can induce ruffling membrane in KB cells and is predominantly expressed in the brain during development. Here, we characterize the molecular nature of STEF and its involvement in neurite growth. Deletion analyses revealed distinct roles for individual domains: PHnTSS for memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
84
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 42 publications
8
84
2
Order By: Relevance
“…Control siRNA had no effect on these parameters. In so doing, they complement and extend the results of recent studies that demonstrated an important role for STEF and Rac1 in mediating neurite outgrowth from neuroblastoma cells (21). Taken together with studies on Cos-7 cells, the observations in neuronal cells offer compelling evidence that BDNF induces changes in cell shape through a signaling pathway that depends critically on direct TrkB-mediated Tyr-829 phosphorylation of Tiam1 with resulting activation of Rac1.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Control siRNA had no effect on these parameters. In so doing, they complement and extend the results of recent studies that demonstrated an important role for STEF and Rac1 in mediating neurite outgrowth from neuroblastoma cells (21). Taken together with studies on Cos-7 cells, the observations in neuronal cells offer compelling evidence that BDNF induces changes in cell shape through a signaling pathway that depends critically on direct TrkB-mediated Tyr-829 phosphorylation of Tiam1 with resulting activation of Rac1.…”
Section: Resultssupporting
confidence: 70%
“…Overexpression of Tiam1 promotes the formation of lamellipodial structures in fibroblasts and neurites in neuroblastoma cells (14). STEF͞Tiam2, another Rac1-GEF, is highly homologous with Tiam1 and also increases neurite outgrowth (21). Because endogenous Tiam1 was detected at high levels in Cos-7 cells, we set out to study whether Tiam1 mediated BDNF-induced Rac1 activation in these cells.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of Rac1 GTPase can induce EMT, and regulate the expression of MMPs (Mack et al, 2011). It is reported that TIAM2 is required for the activation of Rac1 GTPase in neuronal and skin papilloma cells (Matsuo et al, 2002;Rooney et al, 2010). Here, we found that TIAM2 could induce the activation of Rac1 in NSCLC cells, further confirming the role of TIAM2 in the regulation of Rac1 activation.…”
Section: Discussionsupporting
confidence: 74%
“…The involvement of TIAM1 in the invasion and metastasis has been well studied in many tumors (Minard et al, 2004). As the homology of TIAM1, TIAM2 has been shown to regulate the reorganization of actin cytoskeletal in neuronal cells (Matsuo et al, 2002;Goto et al, 2011). Recent studies have found that TIAM2 promotes proliferation and invasion in liver cancer cells (Chen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although A-class ephrins are not highly expressed in the developing mouse cortex (Yun et al, 2003), it is important to examine the expression of Tiam1 and Ephexin, two exchange factors having opposing effects on the neurites motility, in the cortical region. Furthermore, we also have to consider a homologous protein of Tiam1, STEF, another GEF for Rac1, because STEF is also expressed in the cerebral cortex of developing mice (Matsuo et al, 2002;Kawauchi et al, 2003). We detected the association of the PHnTSS domain Because the PHnTSS region of Tiam1 is highly homologous to the PHnTSS domain of STEF, these Tiam1 fragments may also work as dominant-negative mutants for STEF.…”
Section: Discussionmentioning
confidence: 99%